Simulators for sensor-guided autonomous systems - Chen, I-Ming. (2008)
Computer simulation of complex systems or processes, such as manufacturing workcells and traffic flow control, becomes an essential part of the actual implementation because the effort, time and cost needed to perform complicate hardware prototyping and testing are tremendous. This is especially true for sensor-guided autonomous systems that involve both continuous control and discrete event control to interact with the environment, for instance, intelligent manufacturing systems and vision-guided autonomous robots. Current commercial packages that can simulate such systems are costly and mostly run on expensive high-end graphical workstations. Thus, the overhead of installation hampers the widespread of simulation systems in the R & D department of small and medium sized companies and educational institutions.